The Role of Legal Conflictology in the Training of Lawyers - Kaija, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Conflicts are everyday occurrences in people’s lives, social groups and international relations. In all historic times, in all cultures, groups and countries, the quest for peace has been ongoing. Costs incurred because of conflicts are very high: human suffering, economic losses and moral degradation. Conflict resolution, transformation, mediation and management describe the scientific and multi-disciplinary approach of legal conflictology. The aim of this article is to popularize and develope in Latvia a new branch of science, education and practice - legal conflictology.